The Effectiveness of the Discovery Learning Model on the Metacognitive Ability of the Students of SMP Negeri Satap Lesten Gayo Lues Regency - Nora Fadillah; Marah Doli Nasution; Zulfi Amri (JMEA : Journal of Mathematics Education and Application, 2022)
Research is research involving one class as an experimental class. The purpose of this study was to determine the effectiveness of using a discovery learning model to apply mathematical learning with Pythagorean material. It is related to the metacognitive abilities of eighth-grade middle school students. This study is a quasi-experimental study. The population in this study were all grade VIII students of SMP Negeri Lasten Kab, Gayo Lues for the academic year 2020/2021, which amounted to 9 classes. The sample was drawn using cluster random sampling so that a sample of Class VIII-1 students was obtained from 17 female students and 15 male students. men, as the experimental class without a control class group. The research test instrument used was an initial mathematical ability test and a student's metacognitive ability test by learning the Discovery Learning model. Analysis, descriptive analysis and inferential analysis of the data used. From the research conducted, findings (1) indicate that students' initial math skills remain low prior to applying the discovery learning model for learning. (2) The metacognitive ability scores of the learning models were found to be in the good category. Based on the results of the research conducted, it can be said that learning using the discovery learning model effectively improves the metacognitive abilities of the class VIII SMP Negeri Lasten Kab, Gayo Lues.